Ensuring the Fulfillment of Elderly Rights in Institutional Care: An Empirical Legal Review through the Lens of Islamic Law in Medan - Fachrul Dhamanhuri Herman; Sukiati Sukiati; Imam Yazid (Bulletin of Indonesian Islamic Studies, 2025)
This study aims to analyze the fulfillment of the human rights of the elderly in nursing homes in Medan City as part of social protection for the elderly group. The background of the research is based on the increasing number of elderly people which has implications for the high need for adequate social services and protection. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that nursing homes play an important role in fulfilling the basic rights of the elderly, especially related to physical, psychological, and social needs. However, there are still various obstacles such as limited professional staff, infrastructure, and adequate budget support. This study concludes that the fulfillment of the rights of the elderly in nursing homes in Medan City has been carried out but is not optimal, so that policy strengthening, improving service quality, and cross-sector collaboration are needed to realize the welfare of the elderly more comprehensively. This research is expected to provide a realistic picture of the implementation of the human rights of the elderly in nursing homes, while also assessing the role of the state and society in ensuring a decent, dignified, and humane life for the elderly. Furthermore, it will provide input for policymakers and nursing home managers to ensure that services for the elderly are increasingly oriented toward respecting their human rights.